È possibile. Trittico su luce e ombra - Vitiello, Vincenzo (Bollettino Filosofico, 2017)
The most beautiful poetry by Goethe about the birth of Being from Love, a scherzo in verses by Kandinskij about the Beginning that is always after itself, the poetical reflection by Valéry on the encounter between the Jeune Parque with the philosopher: three “movements” from Shadow to Light, from Light to Shadow. Three “narrations” of the experiencing  the limit of thinking, of telling, of living in the suggering joy of love, in the playful and vain research of what comes towards us, in the gaze getting lost dans l’obscur de la vie. Three “pictures” of the “possible”.